Synthesis, characterization, and optical properties of well-defined N-doped, hollow silica/titania hybrid microspheres - Song, Xuefeng (Langmuir : the ACS journal of surfaces and colloids, 2007)
Well-defined nitrogen-doped, hollow SiO2/TiO2 hybrid spheres were successfully prepared through a two-step sol-gel synthesis combined calcination process using triethylamine as the nitrogen source. In this approach, polystyrene (PS)/silica microspheres were first synthesized. Subsequently, the amine-treated PS/SiO2/TiO2 hybrid spheres were obtained by sol-gel method. Finally, the elimination of the PS core, nitrogen-doping process, and crystallization of amorphous TiO2 were simultaneously conducted in the calcination process to acquire the final products. The as-prepared hybrid spheres were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared (FTIR) spectroscopy. The results of XRD, FTIR, and XPS spectra indicated that nitrogen was really doped into the anatase TiO2 shell and confirmed that most nitrogen dopants might be present in the chemical environments of N-Ti-O and Ti-N-O. It was found that the absorption shoulder of nitrogen-doped hollow SiO2/TiO2 hybrid spheres vastly shifted to the visible region up to around 530 nm. The photoluminescence (PL) bands showed spectral lines at about 421, 472, and 529 nm, which were attributed to the self-trapped excitons, F and F+ centers. Moreover, the intensity of the PL spectra band of hollow SiO2/TiO2 hybrid spheres increased with as the amount of titanium tetrabutoxide (TBOT) precursor increased. However, the doping of nitrogen into hollow SiO2/TiO2 hybrid spheres led to the drastic quenching of photoluminescence because of the increase in the separation efficiency of the photoinduced electron and hole pairs